التعليم العالي في الوطن العربي بين الواقع والمأمول - خليفي, سامية; عليلي, نادية (جامعة الوادي University of Eloued, 2020)
تهدف هذه الورقة البحثية إلى التعرف على واقع مؤسسات التعليم العالي في الوطن العربي ،ويحظى بأهمية كبيرة في أوساط كل المجتمعات وأصبح خيارا إستراتيجيا في منظومة استثمار وتنمية الموارد البشرية والقادرة على تحقيق التقدم في كافة ميادين الحياة ، وتسليط الضوء على أهم التحديات التي تواجهها مؤسسات التعليم العالي في الوطن العربي و وجود محاولات بالنهوض بهذا المجال، وتوصلت الدراسة إلى قيام مؤسسات التعليم العالي بإجراء تغييرات في الذهنية وتطوير الإدارة مع ضرورة إشراك القطاع الخاص في عملية التمويل مع ضمان جودة التعليم العالي و وضع استراتيجيات من خلال التنسيق بين مخرجات الجامعة ومتطلبات سوق العمل للحد من البطالة وهجرة الكفاءات التي تمثل المورد الأساسي للدول. This research paper aims to identify the reality of higher education institutions in the Arab world, and it is of great importance among all societies and has become a strategic choice in the system of investment and development of human resources capable of achieving progress in all fields of life, and to shed light on the most important challenges facing higher education institutions In the Arab world and there are attempts to advance in this field. the study found that higher education institutions make changes in mentality and develop management with the need to involve the private sector in the financing process while ensuring the quality of higher education and developing strategies through coordination between university outputs and the requirements of the labor market to reduce Unemployment and brain drain, which is the main resource for countries.
Higher education in the Arab world, between reality and expectations
مقال
Keywords: تعليم عالي ; مؤسسات; وطن عربي ;تحديات ; آفاق .